(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines effective pedagogical approaches to teaching English for Medical Purposes (EMP) to university-level medical students. Since medical learners require English for clinical communication, academic study, and professional development, the study emphasizes the importance of conducting a detailed needs analysis prior to instruction. The paper discusses core components such as context-based medical vocabulary teaching, role-plays, simulations, integration of soft skills, and the use of authentic and technology-enhanced resources. Methodologically, the article presents sample speaking, listening, reading, writing, and vocabulary activities as well as a four-week syllabus designed to develop communicative competence in clinical scenarios. Practical assessment methods and recommendations are also provided. The findings highlight that interactive, practice-oriented, and clinically relevant tasks significantly improve students’ linguistic confidence and professional communication skills.